Do banks matter for the risk of a firm's investment portfolio? Evidence from foreign direct investment programs - Betschinger, Marie‐Ann (Strategic Management Journal, 2015)
The study explores the role of banks as debt and equity holders for the riskiness of a firm's investment strategy using a panel of J apanese firms in the electronics industry in the period 1992–2004 for the empirical analysis. Based on a conceptual framework grounded in agency and financial intermediation theories, we find that a larger involvement of banks as debt holders in a firm is associated with lower foreign direct investment portfolio risk, while the shareholdings of universal banks increase it, supporting the theoretical predictions . Copyright © 2014 John Wiley & Sons, Ltd.